PATH-33. GERMLINE PREDICTORS OF HEMATOLOGIC TOXICITY IN PATIENTS WITH GLIOMA TREATED WITH CHEMOTHERAPY. (11th November 2019) - Sener, Ugur; Bhatia, Ankush; DeAngelis, Lisa; Mandelker, Diana; Yerram, Prakirthi
Abstract: BACKGROUND: Temozolomide is an alkylating agent commonly used in treatment of gliomas. While this agent is generally well-tolerated, hematologic toxicity is a known complication with grade 3/4 thrombocytopenia in 4% and grade 3/4 neutropenia in 8% of adults. Recent data in several non-CNS malignancies suggested that patients with germline mutations may carry an increased risk of hematological toxicity in the setting of alkylator chemotherapy. We aimed to investigate if germline mutations in glioma patients are associated with myelotoxicity during alkylating chemotherapy. METHODS: In this retrospective single-institution study, we reviewed patients with glioma treated at Memorial Sloan Kettering Cancer Center (MSKCC) who had confirmed germline mutations identified by the institution's Integrated Mutation Profiling of Actionable Cancer Targets (MSK-IMPACT) testing. MSK-IMPACT evaluates DNA for mutations in 76 genes known to be associated with hereditary cancer predisposition. RESULTS: In 283 patients with glioma who underwent MSK-IMPACT testing, 16 distinct germline mutations were identified in 40 (14%) individuals. 27 had high-grade and 13 had low-grade glioma. Median age was 47 (range 1–79), 12 patients were women. 30 patients received temozolomide chemotherapy. Of the patients treated, four (13%) developed severe hematologic toxicity. Two cases of grade 3 neutropenia and four cases of grade 3/4 thrombocytopenia were identified. Temozolomide was stopped during radiation therapy for three patients with grade 4 thrombocytopenia or neutropenia, and dose-reduced in one patient with grade 3 thrombocytopenia. In patients who had hematologic toxicity, germline mutations were identified in genes NBN, ATM, EPCAM, and FANCC. NBN, ATM, and FANCC are involved in DNA repair. EPCAM is involved in cell adhesion. CONCLUSIONS: Hematologic toxicity is a known complication with alkylator chemotherapy. Germline testing may identify patients at increased risk, leading to closer monitoring, modified dosing regimens to minimize myelosuppression, and quicker intervention to prevent interruptions in treatment.